PENGGUNAAN PERMAINAN OLAHRAGA TRADISIONAL DALAM PEMBELAJARAN PENDIDIKAN JASMANI UNTUK MEMBENTUK PERILAKU SOSIAL PESERTA DIDIK - Mudayat, Mudayat (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
The decline in the quality of students' character, such as discipline, responsibility, honesty, and sportsmanship, has become one of the challenges of education in the current era. Physical education and sports have strategic potential as a vehicle for internalizing character values through direct, cooperative, and competitive learning experiences. This study aims to describe the application of character values in physical education instruction and to analyze how this application contributes to students' character formation. The study uses a qualitative, descriptive research approach conducted in a secondary school. The research subjects include physical education teachers and students selected purposively. Data were collected through observation of learning activities, in-depth interviews, and documentation studies (lesson plans, teaching journals, and attitude assessment documents). Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, with triangulation of sources and techniques to ensure data validity. The results showed that the values of discipline, responsibility, cooperation, sportsmanship, honesty, and respect were instilled through the establishment of game rules, team formation, teacher role modeling, and reinforcement and reflection after activities. Students showed positive behavioral changes, especially in compliance with regulations, cooperation, and acceptance of defeat or victory in a mature manner. Supporting factors included teacher commitment and school culture, while the main obstacles included time constraints, infrastructure, and student heterogeneity.